Personalized targeted therapy of moderate and severe atopic asthma in Russia - D. S. Kulichenko; K. S. Pavlova; O. M. Kurbacheva; N. I. Ilina (Медицинский совет, 2022)
Introduction. Taking into account the prevalence of asthma and especially severe atopic asthma which requires carefully selected and expensive therapy, the appearance of the domestic biosimilar omalizumab among biological therapy drugs makes the choice of treatment for this category more affordable. The article presents the results of an observational open prospective clinical trial of the omalizumab biosimilar in severe athopic asthma patients.The purpose of this study was to evaluate the efficacy and safety of the domestic production biosimilar in the real clinical practice.Materials and methods. The study involved 10 adult patients aged 19 to 55 years with a diagnosis of moderate to severe uncontrolled persistent asthma treated with mediun to high dose ICS and second&more controller (ACQ-5 ≥ 1,5, FEV1 < 80% of the predicted normal value). For 26 weeks all patients received the omalizumab. The evaluation of the efficacy was provided taking into account asthma symptoms improvement the results of ACQ-5, FEV1, PEF, asthma exacerbations and the use of health resources. Results. According to the results of data analysis due to omalizumab all patients demonstrated reducing daily asthma symptoms, nocturnal awakening and night time symptom, shortness of  breath and SABA using. An  asthma control improvement was observed after 1 month treatment (Δ ACQ-5 1.6 [1.2; 2.4], p = 0.0002 compared to the baseline data) with a continued tendency to further increase during 6 months of the study. A statistically significant increase in FEV1 was noted (initially, FEV1 56.7% [51.25; 61.8] of the predicted; after 1 month, FEV1 67.5% [63.45; 70.6] of the predicted, p = 0.00003; after 6 months, FEV1 80.6% [80.55; 84.05] of the predicted, p >< 0.001). Omalizumab biosimilar used allowed to reduce the background asthma therapy. No asthma exacerbation was registered due to 26 weeks omalizumab treatment. Conclusions. Based on the results of the study, it was shown that the administration of the omalizumab biosimilar to patients with severe atopic asthma improves control over the symptoms, lung function and reduces the amount of asthma exacerbations, and has a good safety>< 80% of the predicted normal value). For 26 weeks all patients received the omalizumab. The evaluation of the efficacy was provided taking into account asthma symptoms improvement the results of ACQ-5, FEV1, PEF, asthma exacerbations and the use of health resources.Results. According to the results of data analysis due to omalizumab all patients demonstrated reducing daily asthma symptoms, nocturnal awakening and night time symptom, shortness of  breath and SABA using. An  asthma control improvement was observed after 1 month treatment (Δ ACQ-5 1.6 [1.2; 2.4], p = 0.0002 compared to the baseline data) with a continued tendency to further increase during 6 months of the study. A statistically significant increase in FEV1 was noted (initially, FEV1 56.7% [51.25; 61.8] of the predicted; after 1 month, FEV1 67.5% [63.45; 70.6] of the predicted, p = 0.00003; after 6 months, FEV1 80.6% [80.55; 84.05] of the predicted, p < 0.001). Omalizumab biosimilar used allowed to reduce the background asthma therapy. No asthma exacerbation was registered due to 26 weeks omalizumab treatment.Conclusions. Based on the results of the study, it was shown that the administration of the omalizumab biosimilar to patients with severe atopic asthma improves control over the symptoms, lung function and reduces the amount of asthma exacerbations, and has a good safety.